2019
DOI: 10.3390/md17050276
|View full text |Cite
|
Sign up to set email alerts
|

Azaspiracids Increase Mitochondrial Dehydrogenases Activity in Hepatocytes: Involvement of Potassium and Chloride Ions

Abstract: Background: Azaspiracids (AZAs) are marine toxins that are produced by Azadinium and Amphidoma dinoflagellates that can contaminate edible shellfish inducing a foodborne poisoning in humans, which is characterized by gastrointestinal symptoms. Among these, AZA1, -2, and -3 are regulated in the European Union, being the most important in terms of occurrence and toxicity. In vivo studies in mice showed that, in addition to gastrointestinal effects, AZA1 induces liver alterations that are visible as a swollen org… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…62 In this regard, it has been demonstrated that cholesterol levels control the activity of VRAC, because cholesterol depletion increases VRAC activation. 63 Although the involvement of chloride ions in the mechanism of action of azaspiracids has been formerly described, 23,64 the exact mechanism of the interaction of these toxins with chloride channels has never been elucidated; however, overexpression of VDAC proteins after exposure of neuroblastoma cells for 15 h to 15 nM AZA1 has been previously documented. 47 In this work, we demonstrated for the first time that VRAC channels are directly related to the cellular alterations caused by azaspiracids, because intracellular ATP depletion eliminated the increase in chloride channel activation observed in the cells treated with the toxin.…”
Section: ■ Discussionmentioning
confidence: 99%
“…62 In this regard, it has been demonstrated that cholesterol levels control the activity of VRAC, because cholesterol depletion increases VRAC activation. 63 Although the involvement of chloride ions in the mechanism of action of azaspiracids has been formerly described, 23,64 the exact mechanism of the interaction of these toxins with chloride channels has never been elucidated; however, overexpression of VDAC proteins after exposure of neuroblastoma cells for 15 h to 15 nM AZA1 has been previously documented. 47 In this work, we demonstrated for the first time that VRAC channels are directly related to the cellular alterations caused by azaspiracids, because intracellular ATP depletion eliminated the increase in chloride channel activation observed in the cells treated with the toxin.…”
Section: ■ Discussionmentioning
confidence: 99%
“…The azaspiracid group of HAB toxins also results in diarrhetic symptoms. Its mechanism of action is not yet known, but recent evidence suggests that mitochondrial dehydrogenase may be a major target of this toxin group [ 375 ].…”
Section: Impacts Of Ocean Pollution On Human Healthmentioning
confidence: 99%
“…For instance, AZAs modifying hERG activity in vitro could explain at least in part the cardiotoxicity observed in rats after intraperitoneal treatment [ 213 , 214 , 215 ]. Another example could be hepatocytes’ K + and Cl - channels modification in vitro with liver affection in mice following oral exposure to these biotoxins [ 215 , 216 ]. Cytoskeletal rearrangement in the intestinal cell model could also be related to intestinal fluid accumulation in mice [ 16 , 215 ].…”
Section: Mechanism Of Action and Toxicity: The Need For Predefined To...mentioning
confidence: 99%